186 Vitamin and Mineral Supplementation During Gestation does not Influence Milk Yield or Composition During Early Lactation in Grazing or Parlor-Milked Beef Heifers. (12th April 2022) - Baumgaertner, Friederike; Hurlbert, Jennifer L; Bochantin, Kerri A; Menezes, Ana Clara Baiao B; Sedivec, Kevin K; Kirsch, James D; Underdahl, Sarah R; Dahlen, Carl R
Abstract: Two experiments were conducted to evaluate effects of vitamin and mineral supplementation during gestation on milk yield and composition at a single point in time, or via daily milk production during early lactation in beef heifers. Forty-one Angus-based heifers received either a basal ration (CON) or the basal diet plus vitamin mineral supplementation (VTM, 113 gheifer -1 d -1 ) from breeding until parturition. For experiment 1, 29 heifers (12 CON and 17 VTM) were managed as one pasture group after parturition. Using a portable milking machine, heifers were milked at d 56 postpartum between 7 and 10.5 hours after calf removal. For experiment 2, 12 heifers (6 CON and 6 VTM) were acclimated to a free stall barn and milked twice daily for 78 d following parturition. Milk yield was recorded at each milking and samples were collected at d 32, 58, and 78 for component analysis. Data were analyzed using the GLM procedure of SAS. For grazing heifers, milk yield and components ( P ≤ 0.91) did not differ between treatments, with mean yield of 9.95 ± 0.34 kg/d, 4.09 ± 0.11% fat and 2.82 ± 0.04% protein. Twice daily milking data (8.19 ± 0.08 kg/d mean yield with 3.43 ± 0.14 % fat and 3.17 ± 0.03 % protein) revealed that after d 7 milk yield remained similar for the rest of the evaluation period ( P ≥ 0.12); however, protein was greater ( P = 0.02) at d 58 (3.26 ± 0.05%) compared with d 32 (3.10 ± 0.05%) and urea was reduced ( P < 0.0001) at d 78 compared with either d 32 or 58 (11.24 ± 0.55 vs. 18.84 ± 0.55 and 19.10 ± 0.55 mg/dL, respectively). Overall, the successful management of these beef heifers in a dairy facility lays the platform for future work that will establish energy requirements during early lactation for primiparous beef cows.